Penyuluhan Hukum Tentang Pencegahan Tindak Pidana Korupsi Bagi Calon Advokat Perkumpulan Penasihat dan Konsultan Hukum Indonesia Cabang Mataram - Fathur Rauzi; Sukarno (Insan Kreasi Media, 2022)
Corruption is defined as carrying out an action with the intention of obtaining wealth and or profit that is contrary to the rights and obligations of others. This community service program aims to provide enlightenment to Prospective Advocates of the Indonesian Legal Advisory and Consultant Association regarding the Prevention of Corruption for Prospective Advocates. After the service program was carried out by providing legal counseling related to understanding in order to avoid corruption, the training participants who were prospective advocates became more aware and understood the importance of a deep and basic understanding of the elements and concepts of corruption. Then, efforts that can be made to increase public participation in preventing corruption include; system improvement, because a good system can minimize the occurrence of corruption. For example, through online public services, integrated surveillance systems, and so on. In addition, by structuring public services through coordination and supervision of prevention (korsupgah), as well as encouraging transparency of state administrators (PN). Meanwhile, in order to encourage transparency of state administrators (PN), the KPK accepts LHKPN reports and gratuities. In carrying out its coordination tasks, the KPK has the authority to request reports from relevant agencies regarding the prevention of corruption. As for the implementation of its supervisory duties, the Corruption Eradication Commission has the authority to supervise, research, or review agencies that carry out their duties and authorities related to eradicating corruption, and agencies that carry out public services.